Association of G/A Polymorphism, rs266882, in AREI Region of the Prostate-Specific Antigen Gene with Prostate Cancer Risk and Clinicopathological Features - Samzadeh, Mohammad; Hasanzad, Mandana; Jamaldini, Seyed Hamid; Haghdoost, Ali Akbar; Afshari, Mahdi; Ziaee, Seyed Amir Mohsen (Urology Journal, 2012)
PURPOSE: To determine the association of prostate-specific antigen (PSA) 158A/G polymorphism with clinicopathologic characteristics of the disease and prostate cancer (PCa) risk. MATERIALS AND METHODS: Two hundred and six subjects, including 95 patients with PCa and 111 subjects with benign prostatic hyperplasia (BPH), were recruited in this study. Genotyping was performed by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism method. RESULTS: Presence of GG genotype significantly increased the risk of PCa more than 2-fold compared to AG genotype (adjusted odds ratio = 2.4; P = .03). The percentages of G alleles of polymorphisms in patients with PCa were more than that in ones with BPH (odds ratio = 1.2; P = .7). CONCLUSION: The GG genotype of PSA 158A/G polymorphism is a predisposing factor for PCa. But no association was observed between alleles and grade, stage, or age of diagnosis. Similarly, the rs266882 polymorphism was not associated with PSA plasma levels.